2021
DOI: 10.3791/62280
|View full text |Cite
|
Sign up to set email alerts
|

Staining and High-Resolution Imaging of Three-Dimensional Organoid and Spheroid Models

Abstract: In vitro three-dimensional (3D) cell culture models, such as organoids and spheroids, are valuable tools for many applications including development and disease modeling, drug discovery, and regenerative medicine. To fully exploit these models, it is crucial to study them at cellular and subcellular levels. However, characterizing such in vitro 3D cell culture models can be technically challenging and requires specific expertise to perform effective analyses. Here, this paper provides detailed, robust, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Indeed, by allowing the amplification of tumor material while preserving its characteristics as closely as possible, tumoroids will allow unprecedented single-cell -omics approaches to unravel, at genetic-epigenetic-transcriptomic levels, the diversity of tumor cells before and after treatment. Moreover, the relative ease of genetically modifying them to express fluorescent reporters of specific tumoral sub-populations ( Artegiani et al, 2020 ) should help to dissect and monitor over time by 3D imaging ( Gonzalez et al, 2021 ) mechanisms identified as playing a causal role in tumor escape.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, by allowing the amplification of tumor material while preserving its characteristics as closely as possible, tumoroids will allow unprecedented single-cell -omics approaches to unravel, at genetic-epigenetic-transcriptomic levels, the diversity of tumor cells before and after treatment. Moreover, the relative ease of genetically modifying them to express fluorescent reporters of specific tumoral sub-populations ( Artegiani et al, 2020 ) should help to dissect and monitor over time by 3D imaging ( Gonzalez et al, 2021 ) mechanisms identified as playing a causal role in tumor escape.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, RMS_Os were fixed and processed as described before. 78 Immunohistochemistry (IHC) was performed on an automated immunostainer (Ventana discoveryXT, Roche) using rabbit Omni map DAB kit. Organoids’ slides were stained with HPS (Hematoxylin Phloxine Saffron), or the following antibodies: anti-Desmin (1/50, Dako, cat.…”
Section: Methodsmentioning
confidence: 99%
“…FNRMS-derived organoids were fixed and processed as described before 80 . In brief, immunohistochemistry (IHC) was performed on an automated immunostainer (Ventana discoveryXT, Roche) using rabbit Omni map DAB kit.…”
Section: Methodsmentioning
confidence: 99%
“…no. M7240) were applied 30 min at RT, as described previously 80 . Sequential immunofluorescence was performed using OPAL 520 (Survivin, green), OPAL 690 (Ki-67, red), and cells were counterstained with DAPI.…”
Section: Methodsmentioning
confidence: 99%